Considering on lightning electric fields in presence of ground reflection at non-perfect ground - Izadi, Mahdi; Ab Kadir, Mohd Zainal Abidin; Hajikhani, Maryam (De Gruyter Open, 2014)
In this paper, general electric field expressions are proposed to consider the effect of channel base ground reflections and ground conductivity on the electric field components due to lightning. The proposed method can support different current models and functions directly in the time domain without the need to apply any extra conversions. The proposed method is applied on a sample of measured channel base current from triggered lightning experiment and the results are discussed accordingly. The results show that the ground reflection and ground conductivity can have an effect on the peak values of the electric fields whereby the electric field components have a great effect on the widely used coupling models.